Comparison between FFF beams and FF beams for early stage breast cancer's IMRT treatment. (September 2016) - Tas, B.; Durmus, I.F.; Tokdemir Ozturk, S.
Abstract : Purpose: To evaluate monitor unit(MU)s and treatment delivery time for flattening filter free(FFF) beams and flattening filter(FF) beams while planning early stage breast cancer patient's intensity modulated radiotherapy(IMRT) treatment. Methods: Nine early stage breast cancer patients treatment planning calculated using Monaco 5.1® with eight FF beams for IMRT treatment. All patients were planned simultaneously integrated boost (SIB) technique and all plans were normalized 60 Gy dose to the 95% of tumor bed and breast dose was 50 Gy. All plans were reoptimized with FFF beams using the same optimization parameters. 6MV FFF beam had got maximum 1800 MU/minute dose rate, and 6MV FF beams had got maximum 600 MU/minute dose rate. We compared MUs and total delivery time for both plans. Results: We determined an average MUs difference with FFF beams %12 more than FF beams and an average total delivery time difference with FFF beams %2 more than FF beams for early stage breast cancer patient's IMRT planning. Conclusion: The results show that IMRT plans with FFF beams are not decreasing total delivery time for early stage breast cancer patients because of large field size however high dose rate. Therefore, we are treating early stage breast cancer patient's IMRT plan with FF beams in our clinic.